2021
DOI: 10.3390/toxics9100262
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Particulate Matter Exposure Is Associated with Saliva DNA Methylation at Age 15: Applying Cumulative DNA Methylation Scores as an Exposure Biomarker

Abstract: Background: Exposure in utero to particulate matter (PM2.5 and PM10) is associated with maladaptive health outcomes. Although exposure to prenatal PM2.5 and PM10 has cord blood DNA methylation signatures at birth, signature persistence into childhood and saliva cross-tissue applicability has not been tested. Methods: In the Fragile Families and Child Wellbeing Study, a United States 20-city birth cohort, average residential PM2.5 and PM10 during the three months prior to birth was estimated using air quality m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Ideally, a study should include an integrated investigation combining proteinaceous, genetic and/or epigenetic levels. In recent years, a rapid increase has been observed in the number of studies in which integration was successfully applied, as well as in the number of tools developed to facilitate the integration [ 23 , 101 , 102 , 103 , 104 ]. Such an approach optimizes the use of potential health biomarkers in epidemiological studies to reach an in-depth understanding of interrelated or complementary relationships of the biomarkers and of certain disorders as well as to identify potential risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, a study should include an integrated investigation combining proteinaceous, genetic and/or epigenetic levels. In recent years, a rapid increase has been observed in the number of studies in which integration was successfully applied, as well as in the number of tools developed to facilitate the integration [ 23 , 101 , 102 , 103 , 104 ]. Such an approach optimizes the use of potential health biomarkers in epidemiological studies to reach an in-depth understanding of interrelated or complementary relationships of the biomarkers and of certain disorders as well as to identify potential risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Among these developments are the use of poly-epigenetic scores of exposure, which integrate information from multiple CpG sites to provide a record of exposure or to capture a complex trait (93). This approach has been used to examine maternal smoking (9497) glucocorticoid, and prenatal folate exposure during pregnancy (55,98), alongside environmental exposures such as pollution (98). Examining DNAm proxies of inflammation is uncommon, but given the health associations with inflammatory-related DNAm in adult cohorts (47,48,99), and the shared nature of epigenetic changes between mother and infants (64,100), we hypothesised that variance in the neonatal methylome could reflect a convergence of amassed inflammatory burden from different perinatal origins.…”
Section: Discussionmentioning
confidence: 99%
“…Given we have now applied this method to buccal-cell DNAm, it is encouraging to see similar associations between DNAm CRP and brain structural outcomes, especially given that DNAm is highly tissue specific (136), and previous research has reported on cross-tissue differences in magnitude and direction of effects for other traits (137). This cross-tissue approach (where weights were originally created from blood-based DNAm, and later applied to saliva-based composite signatures) has also been adopted in other studies (98,138). While future studies would ideally measure CRP directly from serum or blood spots in infants to enable direct cross-tissue comparisons, saliva has the advantage of being one of the most accessible tissue samples for infant populations, and may be more suitable than other peripheral samples (such as blood) when examining brain and cognitive outcomes owing to the brain and buccal cell shared ectodermal origins (139142).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Changes in DNAm associated with prenatal exposure to PM 2.5 can even be detected in salivary samples as late as at 15 years of age. 31 Of particular note is a study utilizing a large multisite cohort that identified 14 CpG sites at which infant DNAm was associated with prenatal PM 2.5 exposure averaged across pregnancy. 32 While averaging exposures across pregnancy does provide a robust and powerful marker of total PM 2.5 exposure during pregnancy, it is important to consider that the impact of an exposure on a specific health outcome may depend on the timing of that exposure.…”
Section: What This Study Addsmentioning
confidence: 99%